Dynamic collaboration between artist and culture: interactive art applied in Wat Bujang Sugi Folklore as a new dimension - Masanat @ Meramat, Florene Ejot; Shanat, Musdi; Razali, Rosmidahanim (Universiti Teknologi MARA, Perak, 2025)
In this research, the researcher explores the dynamic collaboration in between artist and folklore especially focusing on the interactive art that applied in the context of Wat Bujang Sugi folklore. By Wat Bujang Sugi folklore, the researcher will explore and delve on how artists can use arts as a new dimension art that combine between artist and folklore. This can help the audience understand more about the folklore and engage the audience in a unique and immersive way. Through this research, the researcher will highlight the potential interactive art as a medium for preserving and revitalising folklore as tradition as well as expending the possibilities. This research will using qualitative methods such as interviews and observations to gather data. The insight from artists, folklore experts and audience members involved in the interactive in art project of Wat Bujang Sugi folklore. The objective of the research is to document the process and the outcomes in the collaborative arts by analysing the impact on preserving a promoting folklore, the tradition and culture as well as the artistic innovation with the audience.